Comparison of the clinicopathological characteristics of children with anti-neutrophil cytoplasmic antibody-associated vasculitis with/without infection at diagnosis - Li-Li Long; Mei Tan; Hui Deng; Hui Tang; Xiao-Qing Lin; Miao Zhang; Hui-Ying Deng; Xia Gao (BMC Nephrology)
Abstract Background Infectious episodes contribute to morbidity and mortality in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Renal involvement, also known as ANCA-associated glomerulonephritis (AGN), is frequently observed in AAV. Little is known about whether co-infection at initial diagnosis is associated with renal outcome and prognosis in children with AGN. Methods Clinical and prognostic data for children admitted to our center with AAV from January 2001 to August 2023 were analyzed retrospectively. We compared the incidence of end-stage renal disease (ESRD) and mortality according to infection status at initial diagnosis. Results A total of 33 children with AGN were included in this study, 22 had an infection at the time of AGN diagnosis. A trend toward higher levels of proteinuria in the infected group than in the non-infected group was observed (p = 0.42). Patients in the infected group had higher creatinine and lower eGFR values than those in the non-infected group (p = 0.09). A significant decrease in HGB was observed in the infected group (p < 0.05). There were no significant differences in the baseline values of ALB and complement c3 between the two groups. A similar proportion of patients in both groups required dialysis at the time of diagnosis (27.3% vs. 31.8%). Patients with infection presented with significantly greater ESR and CRP levels (p < 0.05), and the most commonly infected site was the lung. After 6 months of treatment, compared with those in the non-infected group, the median levels of creatinine and proteinuria were higher in the infected group. Besides, lower levels of eGFR and ALB were also observed in the infected group. 5 (45.5%) and 13 (59.1%) patients died or progressed to ESRD, respectively, in the non-infected group and infected group at the last follow-up. Conclusions Infection at initial diagnosis does not affect the outcomes of children with AGN, although it could lead to a reduction in kidney function.